Platelet activation studies on polymeric surfaces - Suzliana Sulaimi (2009)
Platelets are important in the thrombogenicity of biomaterials in blood contacting applications. For long term implantation, polymeric materials need to acquire minimize non-thrombogenic properties and reduction of platelet activation is determinant for the success of any application. Modifying biomaterials surface will influence platelets activity and has been shown to have an effect on thrombosis, however it is not easy to alter the surface due to different responses in the body. Platelet activation effects varies with the nature of topography, in this case, pillars are studied. A series of immunofluorescence staining of platelets was performed to get the optimized parameters; which are 1 wash before stain as shown by the higher intensity and minimal presence of debris as compared to 2 and 0 wash at dilution factors of 1:1 and 4:1 for CD 62P and PAC-1 respectively as the intensity shift between the negative and positive control samples were more significant. Platelets were incubated on PLGA substrates with varying geometric aspects. The results demonstrate that nanostructured surface has lower platelet activation as compared to micron and pristine surface, which signifies the effectiveness of nanofeature in reducing activation. The factors that contributed to reduce activation were narrow spacing, small diameter and high height. The parameter that fits the above condition was aspect ratio. In conclusion, the study highlights the importance of understanding platelet response on nanostructured surfaces and provides an effective tool with which to having reduced activation in the design of blood contacting medical devices.